PENGARUH LIKUIDITAS, SOLVABILITAS DAN STRUKTUR MODAL TERHADAP PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Diza Daffa Ahmadani; Abdul Rohman (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of liquidity, solvency, and capital structure on profitability, as well as examine the role of firm size as a moderating variable in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. Profitability is measured using Return on Assets (ROA), liquidity with the Current Ratio (CR), solvency with the Debt to Asset Ratio (DAR), and capital structure with the Debt to Equity Ratio (DER). Firm size is calculated using the natural logarithm of total assets.The research method is descriptive quantitative with a purposive sampling approach of companies that meet the criteria. Secondary data were obtained from the companies' annual financial reports. The data were analyzed using Multiple Linear Regression and Moderated Regression analysis (MRA) to examine the moderating effects.The results show that liquidity and capital structure have a significant negative effect on profitability, while solvency has a significant positive effect. Firm size was found to moderate the relationship between capital structure and profitability but did not moderate the effect of liquidity and solvency on profitability.This study provides theoretical contributions to the corporate finance literature and practical implications for company management and investors in making strategic financial decisions to improve company profitability.